Challenging the 'offshore hypothesis' for fossiliferous chert artefacts in southwestern Australia and consideration of inland trade routes. (15th January 2017) - O'Leary, Michael J.; Ward, Ingrid; Key, Marcus M.; Burkhart, Mackenze S.; Rawson, Chris; Evans, Noreen
Abstract: Surface scatters containing Eocene chert artefacts are a widespread cultural site type along the Swan Coastal Plain; however, no source rock for the chert is known to exist locally. In the absence of chert outcrops onshore, archaeologists have argued for an offshore source that was subsequently flooded during post-glacial sea level rise. Support for this theory has been the decline or absence of Eocene chert artefacts in deposits younger than 6000 years BP, and the apparent decrease in chert assemblage inland from the contemporary coastline, which may call into question a distal eastern source. This paper presents an alternative theory whereby chert was sourced from the Nullarbor Plain (∼1000 km to the east) and traded east as well as west across southern Australia. Evidence to support this theory includes (1) absence of Eocene age sedimentary strata outcropping on the continental shelf, (2) faunal evidence showing bryozoans imbedded in the Swan Coastal Plain chert, with similar environmental affinities to bryozoans embedded in chert outcropping along the Nullarbor Plain sea cliffs, and (3) geochemical evidence showing a similar geochemical fingerprint between artefacts from the Nullarbor Plain and Swan Coastal Plain. With a peak in fossiliferous chert use around the Last Glacial Maximum, these findings have significant ethnographic implications supporting long distance trade to the east rather than local sourcing of lithic resources by isolated Aboriginal groups. These findings also have chronological implications relating to the use of Eocene fossiliferous chert as a chronological marker for Late Pleistocene to early-Holocene age deposits in southwest Western Australia, albeit with source accessibility following post-glacial sea-level rise still a main factor in the decline in chert use. Highlights: Challenges the long held "offshore hypothesis" which states that chert used to fabricate artefacts was sourced locally. Fossil bryozoans imbedded in the chert artefacts was able to fingerprint the chert source rocks to the Nullarbor Plain. LA-ICPMS was able to find geochemical affinities between artefacts from the Nullarbor Plain and Swan Coastal Plain. Findings highlight the need to revisit the nature of any long-distance trade in fossiliferous chert across southern Australia.